THE ROLE OF AFGHAN UZBEKS IN THE AUTHORITY STRUCTURE OF THE STATE OF AFGHANISTAN: A HISTORICAL ANALYSIS (END OF XIX CENTURY - FIRST HALF OF XX CENTURY) (TAMADDUN NURI JURNALI, 2024)
This article provides information about the role of representatives of the Uzbek nationality living in the country in the administrative structure of the Afghan government from the end of the 19th century to the middle of the 20th century. During this period, the life and activities of many ministers, soldiers, ambassadors, representatives of the government system, who grew up among the local and immigrant Afghan Uzbeks, were analyzed in detail.